From New Regency to Claims of the New Sultan: Legacy of Identity of Siak Sultanate - Abdul Harits Ritonga; Nopriyasman Nopriyasman; Yusmarni Djalius (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
The regional autonomy of Reformasi has given rise to regional identity issues, including restorations of historical sultanates. This paper aims to explain the use of Siak Sultanate legacy, from identity of Siak Regency to claims of new sultan of Siak. This research was conducted based on historical methods through literature exploration and interview. We found that the regency goverment of Siak has successfully utilize some of the sultanate legacy for identity and tourism, while the situation is more complex for the â€˜Sultan’ of Siak. Kekerabatan Resam as â€˜official representative’ of Siak sultanate has no declared restoration, while claims to a new sultan have emerged. The controversy centres on the ambiguity of lineage, power of Kekerabatan Resam, knowledge of traditions, and certain motives driving the restoration.